Yeast culture repairs rumen epithelial injury by regulating microbial communities and metabolites in sheep - Wang, Huihui; Su, Manchun; Wang, Chunhui; Li, Dengpan; Li, Qiao; Liu, Zilong; Qi, Xingcai; Wu, Yi; Zhao, Yongju; Li, Taotao; Ma, Youji (Frontiers in Microbiology, 2023)
This study delves into the impact of yeast culture (YC) on rumen epithelial development, microbiota, and metabolome, with the aim of investigating YC’s mechanism in regulating rumen fermentation. Thirty male lambs of Hu sheep with similar age and body weight were selected and randomly divided into three groups with 10 lambs in each group. Lambs were fed a total mixed ration (TMR; rough : concentrate (R:C) ratio ≈ 30:70 ) to meet their nutritional needs. The experiment adopted completely randomized design (CRD). The control group (CON) was fed the basal diet with high concentrate, to which 20g/d of YC was added in the low dose YC group (LYC) and 40g/d of YC in the high dose YC group (HYC). The pretrial period was 14 days, and the experimental trial period was 60 days. At the end of a 60-day trial, ruminal epithelial tissues were collected for histomorphological analysis, and rumen microorganisms were analyzed by 16S rDNA sequencing and rumen metabolites by untargeted liquid chromatography-mass spectrometry (LC-MS) metabolomics techniques. The results showed that YC improved rumen papilla development and increased rumen papilla length (P < 0.05), while decreased cuticle thickness (P < 0.05). The 16S rDNA sequencing results showed that YC reduced the relative abundance of Prevotella_1 (P < 0.05), while significantly increased the relative abundance of Ruminococcaceae_UCG-005, uncultured_bacterium_f_Lachnospiraceae and Ruminococcus_1 genus (P < 0.05). Metabolomics analysis showed that YC changed the abundance of metabolites related to amino acid metabolism, lipid metabolism and vitamin metabolism pathways in the rumen. In summary, YC might maintain rumen health under high-concentrate diet conditions by changing rumen microbiota structure and fermentation patterns, thereby affecting rumen metabolic profiles and repairing rumen epithelial injury.